Prevalence, awareness, treatment, and control of dyslipidemia and associated factors among adults in Jordan: Results of a national cross-sectional survey in 2019 - Supa Pengpid (2022)
Dyslipidaemia is increasing with low awareness and treatment in low resourced countries. The aim of the study was to evaluate the prevalence, distribution, and correlates of dyslipidaemia and its awareness, treatment, and control among people (18–69 years) in Jordan. In a national cross-sectional survey, a total of 3,132 individuals (mean age: 41.7 years) that took part in the Jordan cross-sectional STEPS survey in 2019 and had complete lipid measurements. Dyslipidemia was defined using the guidelines of the Adult Treatment Panel III. The prevalence of dyslipidemia was 81.6%, 74.0% low high-density lipoprotein cholesterol (HDL-C), 28.2% high triglyceride (TG), 10.1% high total cholesterol (TC) and 8.7% high low-density lipoprotein cholesterol (LDL-C). Among those with dyslipidaemia, 9.3% were aware. Among those who knew, the proportion of lipid-lowering drug treatment was 50.3%, and among those taking lipid-lowering drugs, 25.4% had their dyslipidaemia controlled. In adjusted logistic regression, in both sexes, overweight (AOR: 2.14, 95% CI: 1.49–3.36), obesity (AOR: 2.47, 95% CI: 1.55–3.94), diabetes (AOR: 2.63, 95% CI: 1.30–5.34) were positively and moderate physical activity (AOR: 0.60, 95% CI: 0.37–0.95) was negatively associated with prevalence of dyslipidemia. Older age, overweight, obesity, hypertension, diabetes, and cardiovascular disease were positively associated, and moderate physical activity was negatively associated with awareness of dyslipidemia. Four out of five adults in Jordan had dyslipidaemia and less than one in ten were aware. Several factors associated with the prevalence, awareness, and treatment of dyslipidaemia were identified that can be used to target public health interventions.